Collection development practices in academic libraries in Tanzania - Mwilongo, Kardo Joseph; Luambano, Ireneus; Lwehabura, Mugyabuso J.F. (Journal of librarianship and information science, 2024)
A research paper submitted to the journal of librarianship and information science, Vol. 52, NO.4 of 2020, Pg.1152–1168